The Multiple Scattering of Laser Beam Propagation in Advection Fog and Radiation Fog - Xu, Qiang; Cao, Yunhua; Zhang, Yuanyuan; Yan, Shaohui; Han, Yiping; Wu, Zhensen (International Journal of Optics, 2023)
The laser beams were scattered and attenuated when they propagate in fogs for laser communication, laser remote sensing detection. For different density and droplets distribution of fogs, the laser scatter and attenuation are different, the correspond mechanism need thorough investigation. The characteristics of laser beam scattering in different types of fogs are studied based on the droplet size characteristics of advection fog and radiation fog, the scattering coefficients of droplets with different laser wavelengths(0.86 μm, 0.91 μm, 1.06 μm, 1.3015, and 10.6 μm) are calculated, the multi scattering of laser beam is studied by the Monte Carlo method, the propagation path and scattering direction of photons is analyzed, relations between asymmetry factor, albedo of fog droplets, and the visibility are presented, and the forward scattering intensity and the backward scattering intensity versus scattering angle are gotten and discussed.